From Desks to a Quest: Understanding the Process of Teacher Research - Denise I. Dabisch (Networks: An Online Journal for Teacher Research, 2001)
I conducted my first teacher research study in the spring of 2000 as a requirement for a class I was taking at Arizona State University. This one teacher research study has profoundly changed what I think about teaching. Teaching for me, has become a quest: a never-ending pursuit for those things that matter most to my students and me as we work together in my classes. This essay is my story of how I went from seeking the answer to a rather simple question about my teaching practice to pursuing teaching as a quest. It is a story that shows both the struggles and the rewards of a first time teacher researcher.